Eksistensi Qanun Nomor 3 Tahun 2013 Tentang Bendera Dan Lambang Aceh Dalam Perspektif Teori Norma Berjenang Hans Nawiasky - Purba, Ahmad Rusly (Universitas Islam Sumatera Utara, 2022)
The existence of Qanun Number 3 of 2013 concerning Regional Flags and symbols refers to the provisions of Article 246 and Article 247 of Law Number 11 of 2006 concerning the Government of Aceh, which stipulates that the Aceh government has the authority to stipulate the Aceh regional flag as a symbol of privilege and specificity. But recently published PP. No. 77/2007 concerning Regional Emblems, which in the provisions of Article 6 Paragraph (4) stipulates a prohibition for regions to make regional flags and symbols that resemble prohibited organizations and separatist movements. As a result, the existence of the Aceh flag as regulated in Qanun Number 3 of 2013, is considered contrary to the provisions of Article 6 Paragraph (4) PP. No. 77/2007 concerning Regional Coat of Arms. The use of the Aceh flag in the framework of implementing special autonomy in Aceh is a symbol of the community that shows the identity of the people and region of Aceh, and is not a symbol of sovereignty, this is in accordance with Article 246 paragraph (3) of Law no. 11/2006 concerning the Government of Aceh. Thus, the existence and use of the Aceh flag, seen from its sociological aspect, is a reflection of the Acehnese people themselves. Judging from the process of its formation, the process of forming Qanun Number 3 of 2013 concerning the Aceh Flag and Coat of Arms has met the requirements of legal certainty. When viewed from the legal substance contained therein, there is still a clash of norms between the Qanun on the Aceh Flag and the PP. No. 77/2007 concerning Regional Coat of Arms. Judging from the implementation aspect, until now the provisions of the Qanun have not been implemented, even though they have been ratified by the Aceh government together with the DPRA. Thus, the Qanun concerning the Aceh Flag has not obtained legal certainty in totality, because of the conflicting norms of the legal substance contained in it, so it cannot be implemented. Keywords: Existence, Flag and Coat of Arms of Aceh, Perspective of Tiered Norm Theory.